Malay ornament design in modern Malaysian painting / Haslinda Abd Razak - Abd Razak, Haslinda (Institute of Graduate Studies, UiTM, 2018)
Malaysian Art has been overshadowed with western influence that leads to identity lost. Subsequently, through the National Cultural Congress in 1971, Malaysian art has promoted diverse types of artwork that captures the distinctiveness of Malaysian identity and one of it through Malay ornament design (MOD). However, a study related to ornament design practices, which addresses in fine art scale has not been conducted comprehensively. This study will emphasize on the usage of Malay ornament design in the Malaysian Modern Painting by Malaysian artist. The aim of the study is to identify types of Malay ornament design adapted by Malaysian painters, to gather appropriate samples as to classify the characteristic aspects that adapted through their creative visual art in painting and to analyse the samples of painting by using the visual analysis and trace the elements of ornament design as requested towards the national identity of Malaysia. The samplings are selected from two publications by National Visual Art Gallery (NVAG) permanent collections particularly focusing from year 1980’s until 2008. Twenty-nine paintings have been examined with Ragan (2000) analysis procedures and Sporre (2015) stylistic analysis approaches to investigate these paintings comprehensively…